Onirism in the short story Crveni đurđin by Isak Samokovlija – The boundary between dream and reality - Głombik, Julia (Mundus Slavicus I, 2025)
The article analyzes the role of onirism in Isak Samokovlija’s short story Crveni đurđin, focusing on how the boundary between dream and reality shapes the narrative. The analysis emphasizes the oniric construction of the protagonist Idriz, whose character emerges gradually through the perspective of the narrator. Idriz, his home, garden, and family members are depicted in an almost dreamlike atmosphere of mystery, beauty, and harmony, which is later disrupted by the revelation of his tragic love story with Malka and the symbol of the red dahlias (Crveni đurđin), representing memory, love and loss. The story intertwines subjective perception, symbolic imagery and multiple narrative voices, culminating in a contrast between the narrator’s idealized vision of Idriz and the townspeople’s view of him as a madman. This polifonic structure questions truth, memory, and the reliability of narration, making Crveni đurđin a rich example of how onirism can serve as both a literary technique and a philosophical reflection on human experience.